Differentiation of financial autonomy of Polish cities from the perspective of regional development - Łyszkiewicz, Magdalena; Świeczewska, Iwona (Zróżnicowanie samodzielności finansowej miast na prawach powiatu w aspekcie rozwoju regionalnego, 2015)
The present paper raises the issues of financial autonomy of Polish cities with regard to the aspect of social and economic development of provinces, in which they are located – the topic being of crucial importance both from the theoretical and practical point of view. The significance of the undertaken research follows mainly from the fact that self-reliance and autonomy of a city in the area of financial management are indispensable conditions for its functioning. What potentially leads cities to harmonious and sustainable development is the fact that they possess legal personality, complete their tasks on their own account, manage their property and have their own, independent of the state finances, financial system. In spite of the fact that the goal of a city is not to make maximum profits but to satisfy collective public needs, the most important aim of local self-government authorities while making financial decisions should be to manage their financial resources in a rational way but, at the same time, to keep in mind the priority of the public interest
Biblioteka Regionalisty, 2015, Nr 15, s. 47-62
Keywords: local government; miasta na prawach powiatu; regional development; financial autonomy; city; rozwój regionalny; samodzielność finansowa